Effects of Weak and Strong Cation Exchange Resins on MoistureUptake Behaviorof Ranitidine Hydrochloride: Effect of resins on hygroscopicity of ranitidine - Khan, Shagufta; Giradkar, Praful; Nakhat, Premchand; Yeole, Pramod (Iranian Journal of Pharmaceutical Sciences, 2007)
The aim of the present research was to study the effects of weak cation exchangeresins, polacrilex with exchangeable H+and polacrillin potassium and strong cationexchange resin sodium polystyrene sulfonate on water uptake behavior of ranitidinehydrochloride. Drug resin complexes (DRC) were prepared and evaluated for thepercentage of moisture gain when placed in a humidity chamber at 40E2 °C and75E5% RH for 17 h as compared to drug and free resins under the same condition.Equilibrium moisture content (EMC) under different humidity conditions and therate and extent of moisture uptake in the presence (15 watt florescence light) andabsence of light under 40E2 °C and 75E5% RH were also calculated for DRCs,drug and unloaded resins. DRC 264 (containing polacrilex with H+) gained minimumweight (10.22%) maintaining free flowing characteristics whereas other resinatesshowed higher weight gain and formation of sticky mass while ranitidine HClturned liquid with gain of 28.11% weight. The rate of moisture uptake by ranitidineHCl was found to increase in the presence of light with slight difference in extent,whereas moisture uptake rate was independent of light in the case of resins. Eventhough DRC 264 contained ranitidine HCl, the moisture uptake rate was unaffectedby light and saturation in moisture gain was seen just at 6 h. Thus, loading ranitidineHCl on polacrilex resin with exchangeable H+significantly improves its moistureresistance and may not require very tight environmental controls during itsformulation.